Analysis of design features of vibratory plate compactors - Mikhail A. Afanasev; Ivan S. Tyuremnov (Вестник СибАДИ)
Introduction. Vibratory plate compactors are soil compaction machines with a flat operating device, which is put into a state of oscillatory motion by a vibration exciter. The variety of designs of vibratory plate compactors is one of the reasons for significant variations in their main parameters for the corresponding mass ranges. In order to improve the design methods for self-propelled vibratory plate compactors, an analysis of existing designs has been made. The impact of design on the technical characteristics of vibratory plate compactors has been analyzed.Materials and methods. The study analyses data on the designs and technical characteristics of vibratory plate compactors, presented on the websites and in accompanying materials of manufacturers, as well as their dealers. A total of 1,137 models of reversible and forward vibratory plate compactors manufactured by Russian and foreign companies were reviewed.Results. The design features of vibratory plate compactors have been identified, the ranges of their main parameters have been established. The relationship between the layout of self-propelled (especially, electric) plate compactors and their technical characteristics and analytical models has been analyzed.Conclusion. The scattered main parameters of reversible and forward plate compactors are partly due to the design features of the plate compactors, such as number of unbalanced shafts, the nature of vibrations, the type of transmission, etc. Most of vibratory plate compactors must be considered as two-mass oscillation systems with elasto-viscous bonds when modeling. A number of electric plate compactors are single-mass oscillation systems, which affects the patterns of their interaction with the ground. The base plate shape influences the magnitude of contact stresses, the number of cycles of load applications to one point of soil in one pass, the compaction depth and maneuverability.